Relative comparison of standalone renewable energy system battery storage requirements for residential, industrial and commercial loads. (1st July 2020) - Prajapati, Sandhya; Fernandez, E.
The application of renewable energy sources is quite popular nowadays on account of favourable economics of generation and provision of clean green energy. However, renewable energy by itself may not be capable of meeting the load requirements due to a mismatch between generation and demand. Thus, for satisfactory performance backup, energy storage is required with renewable sources. This paper investigates the performance evaluation of renewable energy system configurations for different load profiles like commercial, industrial and residential loads. The analysis has been applied as a case study of typical towns in the neighbourhood of Delhi (India) that mushroom in industrial and commercial activity to meet the growing economic demand pressures on the metropolis of Delhi. Three standalone renewable energy systems, i.e., solar-battery, wind-battery, and solar-wind-battery have been chosen to provide the required generation. The three different systems are modelled individually to examine which option will involve the least battery capacity. Additionally, the system most economical for meeting the load demands is evaluated. The analysis shows that the solar-battery system utilises the minimum battery capacity but is most expensive while the wind-battery system is the cheapest but with the highest battery requirements.